Frequency of Newly Diagnosed Diabetes Mellitus in Patients Presenting with ST-Elevation Myocardial Infarction - Shah, Mahnoor; Kamran, Muhammad Ali; Gazder, Noshirwan P.; Saeed, Aena (Biological and Clinical Sciences Research Journal, 2025)
Diabetes mellitus (DM) and myocardial infarction (MI) are two prevalent and closely related conditions that significantly contribute to global morbidity and mortality. Objective: The study also assessed the incidence of recurrent MI, heart failure, and long-term complications in both diabetic and non-diabetic groups. Methodology: This cross-sectional observational study was conducted at Ziauddin Hospital Clifton, Karachi from January 2024 to September 2024. A total of 240 patients were added in the study. Data included demographic details such as age, sex, ethnicity, and medical history. During data collection, the team obtained clinical presentation information through symptom display observation and monitoring of symptom start times, together with the analysis of established MI risk factors, that included hypertension, tobacco use, and heart disease heredity. Results: A total of 240 patients were added in the study, with a mean age of 64.2 ± 9.1 years, compared to 56.3 ± 10.0 years in the non-diabetic group. Hypertension was more prevalent in the diabetic group (90%) compared to the non-diabetic group (70%), while smoking was also higher in the diabetic group (60% vs. 45%). The diabetic group had a higher mean BMI (30.1 ± 4.3 kg/m²) and a significantly higher prevalence of metabolic syndrome (80% vs. 40%). Patients diagnosed with newly onset diabetes were significantly older, with a mean age of 64.2 ± 9.1 years compared to 56.3 ± 10.0 years in the non-diabetic group (p < 0.01). Hypertension was more prevalent in the diabetic group (90%) compared to 70% in non-diabetic patients (p < 0.05), indicating a strong association between high blood pressure and the development of diabetes post-myocardial infarction. Conclusion: It is concluded that while diabetes is not directly responsible for causing ST-Elevation Myocardial Infarction (STEMI), it is a significant risk factor that exacerbates the severity and prognosis of the condition.